2006
DOI: 10.1242/jeb.02535
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal adjustment of energy budget in a large wild mammal, the Przewalski horse (Equus ferus przewalskii) I. Energy intake

Abstract: Large ruminants respond to changing plant phenology during winter by decreasing voluntary food intake, increasing gut passage time and utilizing body fat reserves. It is uncertain, however, how other large mammals with a non-ruminant digestive physiology cope with winter forage conditions. Therefore, we investigated seasonality of energy intake in a large herbivorous wild mammal, the Przewalski horse (Equus ferus przewalskii). Throughout all seasons we used the n-alkane method to measure daily dry matter intak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
50
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 37 publications
5
50
1
3
Order By: Relevance
“…In summer, grazing animals had higher locomotor activity levels compared with winter, when animals were kept on paddocks under semi-natural conditions. Similarly, it has been reported that activity levels in ungulates decrease during low T a and thus reduce energy expenditure substantially (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011). This reduction in activity leading to reduced daily energy demands is also observed in small mammals living in the temperate/arctic zone, such as red squirrels (Tamiasciurus hudsonicus) (Humphries et al, 2005) and least weasels (Mustela nivalis) (Zub et al, 2013), but not kangaroo rats (Dipodomys merriami) (Nagy and Gruchacz, 1994) or white-footed mice …”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In summer, grazing animals had higher locomotor activity levels compared with winter, when animals were kept on paddocks under semi-natural conditions. Similarly, it has been reported that activity levels in ungulates decrease during low T a and thus reduce energy expenditure substantially (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011). This reduction in activity leading to reduced daily energy demands is also observed in small mammals living in the temperate/arctic zone, such as red squirrels (Tamiasciurus hudsonicus) (Humphries et al, 2005) and least weasels (Mustela nivalis) (Zub et al, 2013), but not kangaroo rats (Dipodomys merriami) (Nagy and Gruchacz, 1994) or white-footed mice …”
Section: Discussionmentioning
confidence: 67%
“…It has been postulated that these pronounced seasonal fluctuations in MR are based on a reduction in physical activity and the heat increment of feeding and are not dependent on any reduction of BMR (Mautz et al, 1992;Mesteig et al, 2000). However, studies on red deer (C. elaphus), Alpine ibex (Capra ibex ibex), Przewalski horses (Equus przewalski) and domesticated horses (Equus caballus) revealed a nocturnal hypometabolism that contributes to reduced energy expenditure in late winter when food availability is low (Arnold et al, 2004;Kuntz et al, 2006;Signer et al, 2011;Brinkmann et al, 2012). In these last studies, the assumption of a reduced MR as an adaptation strategy to food shortage and low T a was based on the measurement of activity, heart rate and T b or subcutaneous temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Third, our data strongly support the hypothesis that the relationship between ranging and reproductive effort is fundamentally different over different timescales. Within species, over a lifetime, increased ranging is consistently associated with decreased net energy intake, reproductive effort, and maintenance, both in the wild (27)(28)(29) and in the lab (9)(10)(11)(12). In contrast, among species, over evolutionary time, increased ranging is commonly associated with increased reproductive output (Tables 1 and 2; Fig.…”
Section: Discussionmentioning
confidence: 98%
“…Thus, rodents and birds challenged with decreased food per meter in experimental settings increase their ranging but lose weight and spend less energy on maintenance and reproduction (9)(10)(11)(12)(13)(14), even when B ÏŸ C and feeding is ad libitum. Similarly, daily movement distance increases (16)(17)(18)(19) and body mass and condition decrease (27)(28)(29)(30) during periods of food shortage for mammals in the wild, even though the average estimated food energy gained per meter for most free ranging mammals is over an order of magnitude greater than the travel cost per meter (Fig. 2).…”
mentioning
confidence: 99%
“…However, nutritional requirements are not static; they vary seasonally and among individuals of a species depending on age, sex and reproductive status. Nutrient requirements are generally lower in dormant seasons as a result of physiological and behavioral mechanisms (Kuntz et al 2006, Parker et al 2009), such as altered intake rates, digesta passage rates, diet composition, habitat use, active times, and the timing of growth and reproduction. When resource quality or availability is insufficient, animals draw on body reserves, experiencing a decline in body fat and body protein (Parker et al 2009).…”
Section: Seasonality Of Nutritionmentioning
confidence: 99%